EFFECTIVENESS OF REGIONAL TAX AND RETRIBUTION IN HORSESHOE DISTRIC OF EAST JAVA - Asmandani, vena; Kusumaningrum, Nurcahyaning Dwi; Puspita, Yeni; Wicaksono, Galih; Boedijono, Boedijono (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
The other impact resulted in minor results in the field of taxation, namely a decrease in tax revenues, especially local tax revenues. Thus, local governments are required to adapt by making policies to implement local tax revenues in the midst of the Covid-19 pandemic. The policies carried out by each Regency / City have differences with adjusted conditions for their respective regencies / cities, this can be seen from the intensification and extension strategies carried out by local governments in an effort to optimize regional tax revenues. The type of research used in this research is qualitative research. The location where this research is the Government Agency that handles regional tax and regional retribution, which are located in the Horseshoe region of East Java, namely the Bondowoso Regency Regional Revenue Agency, the Jember Regency Regional Revenue Agency, and the Situbondo Regency Revenue, Financial Management and Assets Agency which has carried out strategies and policies to increase regional tax and regional retribution. The results of this study are the Bondowoso Regency Regional Revenue Agency, the Jember Regency Regional Revenue Agency, and the Situbondo Regency Regional Revenue, Financial Management and Assets Agency which have carried out strategies and policies effectively.